(untitled) (The Review of Diabetic Studies, 2025)
Early-career nurse retention is a critical challenge for healthcare systems globally and is particularly salient in countries implementing workforce nationalization strategies. This study examined the impact of Saudization policies on the retention intentions of early-career Saudi nurses, with a specific focus on policy-related, organizational, professional, and socio-cultural factors. A cross-sectional quantitative design was employed, involving 320 early-career Saudi nurses working across public and private healthcare institutions in Saudi Arabia. Data were collected using a structured questionnaire assessing participants’ perceptions of Saudization policies, organizational support, professional development, socio-cultural influences, and retention intentions. Descriptive analyses revealed consistently high levels of strong agreement (91–95%) across all examined domains. Participants reported highly positive perceptions of Saudization policies, viewing them as enhancing employment opportunities, job security, and career development. Organizational support, including effective leadership, mentorship, manageable workloads, and clear career pathways, emerged as a key determinant of retention. Professional factors such as role clarity, clinical competence, recognition, and access to continuing education further reinforced nurses’ commitment, while socio-cultural support, particularly family encouragement and positive societal perceptions of nursing, strengthened retention intentions. Overall, the findings indicate that early-career nurse retention in Saudi Arabia is driven by the synergistic interaction of national policies, supportive organizational environments, professional fulfillment, and socio-cultural alignment. The study underscores the importance of integrated, multi-level strategies in strengthening nurse retention and advancing the sustainability of the national healthcare workforce.